2016
DOI: 10.1002/lsm.22553
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation, migration, and expression of oral‐mucosal‐healing‐related genes by oral fibroblasts receiving low‐level laser therapy after inflammatory cytokines challenge

Abstract: LLLT can counteract the negative effects of high concentrations of inflammatory cytokines, especially IL-6 and IL-8 on gingival fibroblast functions directly related to the wound-healing process. Lasers Surg. Med. 48:1006-1014, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 30 publications
1
30
0
2
Order By: Relevance
“…The selection of the pore size was based on previous literature studies which used this type of transwell system to evaluate fibroblast migration [14, 15]. It was also considered the characteristics of the fibroblast cell type, such as their size (10–15 um).…”
Section: Methodsmentioning
confidence: 99%
“…The selection of the pore size was based on previous literature studies which used this type of transwell system to evaluate fibroblast migration [14, 15]. It was also considered the characteristics of the fibroblast cell type, such as their size (10–15 um).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated by in vitro studies that phototherapy (PT) using laser light modulates cellular functions, such as cell migration and proliferation, even when these cells were exposed to inflammatory cytokines , indicating that this therapy may have biostimulatory effects from the activation of different cell pathways (MAPK/ERK) that induces cellular proliferation . A recent clinical trial also demonstrated the downregulation of several inflammatory mediators as CXCL8, IL‐8 and nitric oxide in saliva after PBM on patients scheduled for hematopoietic stem cell transplantation and planned treatment consisting of a high‐dose chemotherapy myeloablative conditioning regimen compared to control group .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Góralczyk et al [17] have demonstrated that endothelial cells irradiated at 830 nm secrete less inflammatory mediators, such as TNF-α, and present enhanced cell proliferation when cultured under hyperglycemia conditions. Confirming these results, Basso et al [18] have also shown that PBMT can counteract the negative effects of high concentrations of inflammatory cytokines (TNF-a, IL-1β, IL-6, and IL-8) in gingival fibroblast cell cultures by stimulating their migration and proliferation. These PBMT effects are directly related to the wound-healing process and might contribute to accelerate wound closure processes [18].…”
Section: Pbmt Effect On Different Types Of Cellsmentioning
confidence: 63%
“…Confirming these results, Basso et al [18] have also shown that PBMT can counteract the negative effects of high concentrations of inflammatory cytokines (TNF-a, IL-1β, IL-6, and IL-8) in gingival fibroblast cell cultures by stimulating their migration and proliferation. These PBMT effects are directly related to the wound-healing process and might contribute to accelerate wound closure processes [18].…”
Section: Pbmt Effect On Different Types Of Cellsmentioning
confidence: 63%